2016
DOI: 10.18203/2319-2003.ijbcp20164773
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intravenous Magnesium Sulphate with intrathecal Magnesium Sulphate for post- operative analgesia in orthopaedic patients undergoing extracapsular hip fracture surgery

Abstract: Background: Magnesium sulphate (MgSO4) N methyl D aspartate receptor antagonist has the potential to be an ideal adjuvant for postoperative analgesia via intrathecal or intravenous route. The aim of the study was, we compared the efficacy of two routes of MgSO4 (Intravenous vs intrathecal) as an adjuvant to bupivacaine in subarachnoid block (SAB).Methods: Ninety, American Society of Anesthesiologists physical status 1 or 2 patients, aged 20-60 years, scheduled for hip surgeries under SAB were recruited in depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 15 publications
(15 reference statements)
0
11
0
Order By: Relevance
“…Seven studies demonstrated an overall low risk-of-bias, [8,[10][11][12][13][14][15] while one study was categorized as having a high risk-of-bias, [16] and one study had an unclear risk. [17] In terms of randomization, all included studies provided details about the randomization process and were categorized as having a low risk in this domain. [8,[10][11][12][13][14][15][16][17] Regarding deviations from intended interventions, only 2 studies had an unclear riskof-bias.…”
Section: Type Of Surgery Intervention Control Conclusionmentioning
confidence: 99%
See 4 more Smart Citations
“…Seven studies demonstrated an overall low risk-of-bias, [8,[10][11][12][13][14][15] while one study was categorized as having a high risk-of-bias, [16] and one study had an unclear risk. [17] In terms of randomization, all included studies provided details about the randomization process and were categorized as having a low risk in this domain. [8,[10][11][12][13][14][15][16][17] Regarding deviations from intended interventions, only 2 studies had an unclear riskof-bias.…”
Section: Type Of Surgery Intervention Control Conclusionmentioning
confidence: 99%
“…[17] In terms of randomization, all included studies provided details about the randomization process and were categorized as having a low risk in this domain. [8,[10][11][12][13][14][15][16][17] Regarding deviations from intended interventions, only 2 studies had an unclear riskof-bias. [16,17] Notably, one study exhibited a high risk-of-bias in the domain of missing outcome data.…”
Section: Type Of Surgery Intervention Control Conclusionmentioning
confidence: 99%
See 3 more Smart Citations